2015
DOI: 10.1513/annalsats.201406-257oc
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectasis in Children from Qikiqtani (Baffin) Region, Nunavut, Canada

Abstract: Previous researchers have reported that Canadian Inuit children have markedly elevated rates of LRTI early in life. Our study suggests that this may lead to long-term pulmonary sequelae. Preventing LRTI in Inuit infants may both prevent acute, severe illness and reduce their risk of developing permanent lung damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Many YK children have atypical asthma characterized by wheezing with LRTIs, yet poorly associated with atopy. In a study of 17 Canadian Inuit children with bronchiectasis, asthma was identified as the most common comorbidity . Since asthma involves lower airway inflammation, mucous production, and remodeling, it may be an additional risk factor for worsening bronchiectasis .…”
Section: Discussionmentioning
confidence: 99%
“…Many YK children have atypical asthma characterized by wheezing with LRTIs, yet poorly associated with atopy. In a study of 17 Canadian Inuit children with bronchiectasis, asthma was identified as the most common comorbidity . Since asthma involves lower airway inflammation, mucous production, and remodeling, it may be an additional risk factor for worsening bronchiectasis .…”
Section: Discussionmentioning
confidence: 99%
“…In the US, immune dysfunction was frequently associated with bronchiectasis including that among stem-cell transplant recipients who suffered graft versus host disease [33]. Outside of indigenous Canadian cohorts, where high rates of childhood bronchiectasis are reported, data on aetiology of adult Canadian non-CF bronchiectasis is rather limited and the precise nature of aetiology in this country is largely uncertain [34,35]. In Latin America aetiology is, like elsewhere, driven by infection and influenced by infectious disease epidemiology such as that in endemic TB regions or against backdrops of higher rates of pertussis and measles which in turn relate to the lower vaccine uptake rates.…”
Section: Bronchiectasis In the Americasmentioning
confidence: 99%
“…The most striking variation in bronchiectasis epidemiology is observed among indigenous children of Australia, Alaska, Canada and New Zealand [34,35,[38][39][40]. Here, paediatric populations exhibit exceptionally high rates compared to non-indigenous groups with infant or childhood pneumonia cited as the primary cause in many cases.…”
Section: Geographic Variation In the Epidemiology Of Bronchiectasis Bmentioning
confidence: 99%
“…However, among Aboriginal infants from Central Australia incidence rates reach 200 per 100,000 child‐years . Similarly, although the prevalence of bronchiectasis in those aged 0–14 years in New Zealand is 33 per 100,000; for Pacific Island children in New Zealand it is 160 per 100,000; in Canadian Inuit children in Banff region it reaches 200 per 100,000; while for Aboriginal children from Central Australia and South‐West Alaskan Native children rates are about 1,500 per 100,000 . Thus bronchiectasis remains an important problem among socially disadvantaged indigenous groups, and by extrapolation, for children in developing countries where there is overcrowding, poor hygiene, and limited access to healthcare …”
Section: Burden Of Diseasementioning
confidence: 99%